Ultrasonic Tomography of Immersion Circular Array by Hyperbola Algorithm - Liu Yang; Chunguang Xu; Xianghui Guo; Liping Wang (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
This paper presents a development and research of a non-invasive ultrasonic tomography for imaging gas/liquid two-phase flow. Ultrasonic transmitting and receiving are implemented using a circular array model that consists of 36 transducers. COMSOL Multiphysics® software is adopted for the simulation of the ultrasonic propagation in the detecting zone. Various two-phase flows with different gas distributions are radiated by ultrasonic waves and the reflection mode approach is utilized for detecting the scattering waves after the generation of fan-shaped beam. Ultrasonic attenuation and sound speed are both taken into consideration while reconstructing the two-phase flow images under the inhomogeneous medium conditions. The inversion procedure of the image reconstruction is realized using the hyperbola algorithm, which in return demonstrates the feasibility and validity of the proposed circular array model.